Green shipping onboard: Acceptance, diffusion & adoption of LNG and electricity as alternative fuels in Greece - Olga Sideri; Michalis Papoutsidakis; Theodore Lilas; Nikitas Nikitakos; Dimitrios Papachristos (Journal of Shipping and Trade (JST), 2021)
Today, alternative fuels are seen as a critical area of sustainable technological growth in maritime transport. The International Maritime Organisation (IMO), the United Nations body for maritime issues and other international bodies are in the process of amending and updating the regulations applicable to the shipping industry. Greece is ready to enter the era of liquefied natural gas (LNG) and electricity as marine fuels, as Eastern Mediterranean projects are heading towards adopting these alternative fuels. This study aims to explore the intention of the Greek stakeholders in accepting and using LNG and electricity as alternative fuels. The research objectives are to identify, analyse and evaluate the determinants that influence the intention to accept, diffuse and use alternative fuels, LNG and electricity for marine propulsion, and develop, construct and validate a hybrid model that can be used for future study. This research will clarify possible challenges or barriers to the implementation of technology by stakeholders and contribute to a deeper understanding of the green shipping network. It will also highlight the role of key players in the diffusion phase of technological innovation and the technology itself and its characteristics. Moreover, this research will suggest a unified model using the expansive Technology Acceptance Model (TAM) in conjunction with the Innovation Diffusion Theory (IDT) and external variables affecting LNG and electricity 1) to investigate the intent of implementing the use of such alternative fuels and 2) to inform policymakers concerning sustainable shipping.
Keywords: 650; Electricity; Innovation diffusion theory (IDT); Liquefied natural gas (LNG); Technology acceptance model (TAM)